Cell Adhesion Molecule Close Homolog of L1 (CHL1) Guides the Regrowth of Regenerating Motor Axons and Regulates Synaptic Coverage of Motor Neurons - Guseva, Daria; Jakovcevski, Igor; Irintchev, Andrey; Leshchyns’ka, Iryna; Sytnyk, Vladimir; Ponimaskin, Evgeni; Schachner, Melitta (Frontiers in Molecular Neuroscience, 2018)
The close homolog of L1 (CHL1) is a cell adhesion molecule involved in regulation of neuronal differentiation and survival, neurite outgrowth and axon guidance during development. In the mature nervous system, CHL1 regulates synaptic activity and plasticity. The aim of the present study was to evaluate the influence of CHL1 on peripheral nerve regeneration after trauma. Using the established model of mouse femoral nerve regeneration, CHL1 knock-out mice were investigated in comparison to the wild type littermates. First, non-injured mice of both genotypes were compared regarding the synaptic phenotypes in the corresponding spinal cord segment. While no differences in phenotypes were detectable in the femoral nerve, corresponding segments in the spinal cord were observed to differ in that inhibitory perisomatic innervation of motor neurons was increased in CHL1-deficient mice, and numbers of perisomatic cholinergic synapses on motor neuronal somata were reduced. Regarding the femoral nerve after injury, CHL1-deficient mice demonstrated preferential motor axon regrowth into the saphenous versus quadriceps branch after nerve transection upstream of the nerve bifurcation by 8 weeks after transection, indicating decreased preferential motor re-innervation. Furthermore, in injured wild-type mice, enhanced CHL1 expression was observed in regenerating axons in the proximal nerve stump upstream of the bifurcation at days 1, 3, 5, 7 and 14, and in the distal stump at days 7 and 14 after injury, when compared to non-injured mice. Injury-related upregulation of CHL1 expression was more pronounced in axons than in Schwann cells. Despite a more pronounced capacity for preferential motor axon regrowth in wild-type versus mutant mice, only a tendency for difference in recovery of motor functions was observed between genotypes, without statistical significance. Taken together, these results indicate that CHL1 is involved in peripheral nerve regeneration, because it guides regrowing axons into the appropriate nerve branch and regulates synaptic coverage in the spinal cord.